2021
DOI: 10.1111/iere.12533
|View full text |Cite
|
Sign up to set email alerts
|

Choked by Red Tape? The Political Economy of Wasteful Trade Barriers

Abstract: Red-tape barriers (RTBs) are an important source of trade costs, but have received little scholarly attention. Here we take a first step toward a theory of RTBs, and show that their implications are very different from those of more traditional trade barriers.Our model highlights that RTBs have important impacts on the extensive margin of trade, and yields rich predictions on how changes in the political-economic environment and product characteristics affect RTBs. Taking into account the endogenous response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(108 reference statements)
1
10
0
Order By: Relevance
“…The final two assumptions rule out the possibility that the consumption externality is so significant relative to the real expenditure that it is optimal for the government to impose maximum standards. Moreover, higher product standards always reduce the negative externality and hence should not be considered the type of "redtape barriers" studied in Maggi et al (2022). Overall, Assumption 1 is broadly consistent with the role of standards in many GATT/WTO disputes.…”
Section: Equilibrium For Given Product Standardssupporting
confidence: 56%
“…The final two assumptions rule out the possibility that the consumption externality is so significant relative to the real expenditure that it is optimal for the government to impose maximum standards. Moreover, higher product standards always reduce the negative externality and hence should not be considered the type of "redtape barriers" studied in Maggi et al (2022). Overall, Assumption 1 is broadly consistent with the role of standards in many GATT/WTO disputes.…”
Section: Equilibrium For Given Product Standardssupporting
confidence: 56%
“…It is evident from Figure 1 that RTBs can be prohibitive levels of trade even under δ = 0 and e = 0. In Maggi et al (2022), based on a perfectly competitive market, e had to be sufficiently large for RTBs to occur, but in the oligopolistic competition model in this paper, RTBs occur even when e is zero. However, as we will discuss later, we will focus on the interior point solution of θ * , in which the levels of e and δ play an important role in obtaining the interior point solution.…”
Section: Equilibriummentioning
confidence: 96%
“…This kind of non-tariff barriers are called "red-tape barriers (RTBs)" and have attracted much attention in recent years. Maggi et al (2022) are, to the best of our knowledge, the first theoretical study to explicitly examine the relationship between international trade and RTBs. They constructed a small open economy model based on the simplified Grossman and Helpman (1994) political economy model, which they considered as a trade barrier intentionally set by the government, and found that RTBs can occur endogenously in the presence of rent-seeking against producer surpluses.…”
Section: Introducrtionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 While trade facilitation leads to a reduction in red tape barriers (RTBs), tariff reductions can be associated with protectionist backlashes through increases in RTBs (Maggi et al, 2022). See also Beverelli et al (2019) for a more general analysis of 'trade policy substitution', defined as the use of non-tariff measures (NTMs) to restore former levels of tariff protection.…”
Section: Impact Of Trade Facilitation On Trade Costsmentioning
confidence: 99%